Recent Stressful Life Events in Euthymic Major Depressive Disorder Patients: Sociodemographic and Clinical Characteristics - Serafini, Gianluca; Gonda, Xenia; Canepa, Giovanna; Geoffroy, Pierre A.; Pompili, Maurizio; Amore, Mario (Frontiers in Psychiatry, 2020)
Background: Stressful life events (SLE) may influence the illness course and outcome. This study aimed to characterize socio-demographic and clinical features of euthymic MDD outpatients with SLE compared with those without. Methods. The present sample included 628 (mean age=55.1±16.1) currently euthymic MDD outpatients of whom 250 (39.8%) reported SLE and 378 (60.2%) did not. Results: After univariate analyses, outpatients with SLE were most frequently widowed and lived predominantly with friends/others. Moreover, relative to outpatients without SLE, those with SLE were more likely to have a family history of suicidal behavior, manifested melancholic features, report a higher COPE positive reinterpretation/growth and less likely to have a comorbid panic disorder, residual interepisodic symptoms, used psychiatric medications, and currently use antidepressants. Having a family history of suicide (OR=12.017; p=≤.05), having used previous psychiatric medications (OR=2.784; p=≤.05), and using less frequently antidepressants (OR=.307; p=.001) were significantly associated with SLE after regression analyses. Mediation analyses showed that the association between current use of antidepressants and SLE was mediated by previous psychiatric medications. Conclusion: Having a family history of suicide, having used previous psychiatric medications and using less frequently antidepressants is linked to a specific “at risk” profile characterized by the enhanced vulnerability to experience SLE.